PENGARUH TINGKAT PENGANGGURAN TERBUKA DAN INFLASI TERHADAP PDRB RIIL TAHUN 2002–2022 KOTA MEDAN - Siregar, Selamat (Majalah Ilmiah METHODA, 2023)
The purpose of this research is the influence of inflation and open unemployment rate on the growth of Real GRDP of Medan City. The sample used is the data of inflation variable and open unemployment rate variable and Real GRDP growth variable of Medan City from 2007 to 2022. The results of the study obtained that the inflation variable has no significant effect on the growth of Real GRDP of Medan City, the open unemployment rate variable has no significant effect on the growth of Real GRDP of Medan City, together the inflation variable and the open unemployment rate have no significant effect on the growth of Real GRDP of Medan City. and the influence of the inflation variable and the open unemployment rate variable on the growth of Real GRDP is 3.5%, the remaining 96.5% is explained by other variables or factors not discussed in this study.